Modeling and experimental study of inverse suspension polymerization of acrylic acid and trimethylolpropane triacrylate for hydrogel production. - Olivo Arias, Liliana Patricia (2015)
In the present work, a super water-absorbent poly(acrylic acid) was synthetized by inverse suspension polymerization, using Span60 as the dispersant, toluene as the dispersing organic phase, trimethylolpropane triacrylate as the crosslinking agent, and sodium persulfate as the initiator. The synthesis was conducted in a small-scale glass reactor operated in semi-batch mode. The following reaction conditions were evaluated: effects of initiator concentration, temperature, percentage of multifunctional cross-linker agent and monomer concentration. Also, two important properties were determined, conversion and gel fraction. A kinetic model including a population balance was employed to simulate the process. The proposed model uses the numerical fractionation technique and is capable of predicting the pre-gel and post-gel properties, the effect of the crosslinking agent level on the polymer properties and the dynamic of gelation. The model was compared with the experimental results and showed a satisfactory representation of the system after parameter adjusting.